Emerald Ash Borer Specific Gene Silencing Has No Effect on Non-target Organisms - Pampolini, Flavia; Rieske, Lynne K. (Frontiers in Agronomy, 2020)
The sequence complementarity of the RNA interference (RNAi) pathway allows for targeted suppression of genes essential for insect survival, and enables development of pest management strategies specific to a given species while reducing the likelihood of adversely impacting non-target organisms (NTOs). The feasibility of manipulating the RNAi pathway to cause mortality in the highly invasive emerald ash borer (EAB) has been demonstrated. Here the spectrum of activity of three double stranded RNAs (dsRNAs) targeting the genes hsp, shi and sn-rnp in EAB was evaluated in model insects representing five functional guilds including herbivore, predator, detritivore, pollinator, parasitoid; the last represented by the classical biological control agents currently deployed for EAB management in North America. All NTOs were exposed to EAB-specific dsRNAs in diet bioassays that measured potential lethal effects. Gene expression and in silico analysis were also assessed on NTOs for which gene sequences were publicly available. Bioassays demonstrated no lethal effects on our model insects, suggesting a narrow spectrum of activity for the three EAB-specific dsRNAs evaluated. The gene expression and in silico analyses suggest potential sublethal effects on our model pollinator; however we found no effects on insect survival. Overall, our results suggest no adverse effects of the RNAi strategy targeting EAB genes on the survival of the selected non-target organisms we evaluated. The results from this study provide guidance for future RNAi risk analyses that will allow this technology to move forward to a deployment stage.